2020
DOI: 10.1038/s41598-020-71033-7
|View full text |Cite
|
Sign up to set email alerts
|

An extended logistic model of photodynamic inactivation for various levels of irradiance using the example of Streptococcus agalactiae

Abstract: Irradiance is an important factor influencing the acceleration of microorganism mortality in photodynamic inactivation (pDi) processes. experimental observations of pDi processes indicate that the greater the irradiation power is, the faster the decrease in the population size of microorganisms. However, commonly used mathematical models of PDI processes usually refer only to specific values of irradiance without taking into account the influence of change in irradiance on the dynamic properties of inactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…Whereas it is to be expected and shown that use of higher irradiance 405-nm light levels will increase the rate of microbial inactivation (54), the data in this paper establish that lower levels of 405-nm light are actually more germicidally efficient. The log 10 reductions and GE values shown in Table 1 indicate that lower irradiance 405-nm light is more efficient on a per unit dose basis for phage inactivation in comparison to that of equivalent higher irradiance exposures.…”
Section: Discussioncontrasting
confidence: 52%
“…Whereas it is to be expected and shown that use of higher irradiance 405-nm light levels will increase the rate of microbial inactivation (54), the data in this paper establish that lower levels of 405-nm light are actually more germicidally efficient. The log 10 reductions and GE values shown in Table 1 indicate that lower irradiance 405-nm light is more efficient on a per unit dose basis for phage inactivation in comparison to that of equivalent higher irradiance exposures.…”
Section: Discussioncontrasting
confidence: 52%
“…The dose–exposure time relationship in the context of phototherapy is an important issue. We have knowledge from the previous studies of our research group ( 81 ) that the irradiation power influences mortality dynamics. We have observed that the greater the irradiation power, the greater the bacterial mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The current study describes aPDI employing a harmless photoactive compound, i.e., rose bengal (RB), which was used in our previous mechanistic studies concerning aPDI treatment [ 21 , 42 , 43 ]. RB is a xanthene dye, which has been widely applied as a photoactive compound in photodynamic treatment [ 15 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%